2021
DOI: 10.1111/are.15200
|View full text |Cite
|
Sign up to set email alerts
|

Application of biodegradable polymers as carbon sources in ex situ biofloc systems: Water quality and shift of microbial community

Abstract: Aquaculture systems are becoming more intensive to increase economic efficiency (Ren et al., 2019). Large amounts of feed are put into the systems to enhance the growth of cultured animals, which leads to an elevated concentrations of organic waste from uneaten feed and faeces. Ammonia is produced when those organic waste is decomposed (Li & Boyd, 2016). The conversion methods for removing ammonia nitrogen in aquaculture systems are photoautotrophic removal by algae, autotrophic bacterial conversion of ammonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…In all analysed samples, the two functional groups exhibiting the highest abundance were chemoheterotrophy and aerobic chemoheterotrophy (Figure 1), a pattern that has been commonly observed in studies assessing the functional profile of the water bacterial community in shrimp farming, both in conventional (Ding et al, 2021; Vinothkumar et al, 2021) and in BFT systems (Zhu et al, 2021), in addition to ex situ BFT applications (Kokkuar et al, 2021) and in the sediment of aquaculture integrated systems employing fish and shellfish (Zheng et al, 2018). Super‐intensive zero water exchange aquaculture production systems, such as BFT, are characterized by nutrient enrichment and accumulation of organic matter (Avnimelech, 2015; Samocha, 2019), which could favour this type of metabolism, as chemoheterotrophy characterizes bacteria that use organic chemical substances as a source of energy and organic compounds as their main source of carbon (Chan, 2003).…”
Section: Variable Treatment P‐value Heterotrophic Maturesupporting
confidence: 61%
“…In all analysed samples, the two functional groups exhibiting the highest abundance were chemoheterotrophy and aerobic chemoheterotrophy (Figure 1), a pattern that has been commonly observed in studies assessing the functional profile of the water bacterial community in shrimp farming, both in conventional (Ding et al, 2021; Vinothkumar et al, 2021) and in BFT systems (Zhu et al, 2021), in addition to ex situ BFT applications (Kokkuar et al, 2021) and in the sediment of aquaculture integrated systems employing fish and shellfish (Zheng et al, 2018). Super‐intensive zero water exchange aquaculture production systems, such as BFT, are characterized by nutrient enrichment and accumulation of organic matter (Avnimelech, 2015; Samocha, 2019), which could favour this type of metabolism, as chemoheterotrophy characterizes bacteria that use organic chemical substances as a source of energy and organic compounds as their main source of carbon (Chan, 2003).…”
Section: Variable Treatment P‐value Heterotrophic Maturesupporting
confidence: 61%
“…Therefore, it is speculated that although the impact of microplastics on B. calyciflorus may be deepened due to bioaccumulation [ 78 ], the associated bacterial community has improved the tolerance of B. calyciflorus to plastic pollution through a specific composition. Chemoheterotrophy and aerobic chemoheterotrophy can use organic matter to meet all or major carbon requirements under different oxygen conditions [ 79 ], which are the most dominant putative functions predicted by various biologically associated bacterial communities [ 71 , 80 , 81 ]. Nitrogen is the other most important element in a lake ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…The findings revealed that glucose and molasses were the most effective in both growth performance and water quality. Additional studies that investigated carbon sources are [ [114] , [115] , [116] ]. Similarly, more researchers studied the impact of certain bacteria species to show their efficacies in BFT [ 117 ].…”
Section: Bft Vs Clearwater Shrimp Culturementioning
confidence: 99%